Design and installation of an automatic shade mesh control system, case strawberry cultivation (Fragaria sp.) - Romantchik Kriuchkova, Eugenio; López Cañtens, Gilberto; Chávez Aguilera, Noel; Flores L., Diego E. (Revista Mexicana de Ciencias Agrícolas, 2018)
At the national level, the application of electronic systems of automatic control in the processes of agricultural production is becoming more frequent. The development and application of automatic control systems allow the adaptation of cultivation techniques to environmental conditions, in order to achieve a more profitable and rational crop in small areas of the same agricultural exploitation. This work contemplates the development and evaluation of an automatic control system to control the opening or closing of a shadow mesh based on the incident radiation in the crop. An algorithm and program that automates the placement of the shadow mesh was developed with the help of a programmable logic controller (PLC Millenium III) for ease of implementation. The developed system was applied to the strawberry crop (Fragaria sp.). Tests and evaluation were carried out with three strawberry beds: open field, fixed mesh and mobile mesh controlled according to the radiation. The shadow mesh opens if the radiation is less than 400 W/m2 or closes if the amount of radiation is greater than 600 W/m2 when measured with a sensor, in addition it can be opened and closed manually to carry out the harvest and the maintenance. One of the results obtained is that the production in the bed under the mobile mesh is greater in 12.88% than in the fixed mesh and in 37.42% than in the open field.